2011
DOI: 10.1097/pec.0b013e3182131438
|View full text |Cite
|
Sign up to set email alerts
|

Parental Sex and Age-Their Effect on Pain Assessment of Young Children

Abstract: Fathers and mothers do not differ in their evaluation of their children's rating of pain. Younger parents, compared with older ones, tend to evaluate pain as more severe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Notably, we found that this effect was driven by female participants. This finding is in some tension with that reported by Moon et al (2008), who found that fathers, but not mothers, rated the pain of their sons higher in a cold pressor task, as well as Rosenbloom et al (2011), who found no difference between fathers and mothers in ratings of their children's pain. However, the present study did not assess parental judgments of their own children's pain, but rather adult ratings of an unrelated child's pain.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Notably, we found that this effect was driven by female participants. This finding is in some tension with that reported by Moon et al (2008), who found that fathers, but not mothers, rated the pain of their sons higher in a cold pressor task, as well as Rosenbloom et al (2011), who found no difference between fathers and mothers in ratings of their children's pain. However, the present study did not assess parental judgments of their own children's pain, but rather adult ratings of an unrelated child's pain.…”
Section: Discussioncontrasting
confidence: 84%
“…To date, this possibility has received little empirical attention. Among the studies that do exist, the primary focus has often been on the gender of the adult observer (e.g., comparing pain ratings of mothers and fathers; Rosenbloom et al, 2011;Vervoort, Huguet, Verhoeven, & Goubert, 2011). By contrast, when the child's gender has been the focus, the child's actual and perceived gender are typically confounded, because the child's gender is known to the adult (e.g., Moon et al, 2008).…”
Section: Gender Bias In Pediatric Pain Assessmentmentioning
confidence: 99%
“…Also, we analysed pain experiences reported by parents without formally assessing sex/gender interactions in parental perceptions of pain and suffering. There are conflicting findings on whether mothers and fathers report girls' and boys' pain experiences differently (Earp et al, 2019 ; Moon et al, 2008 ; Rosenbloom et al, 2011 ). In this cohort, we ran the same analysis using only mother reported profiles and the estimates remained similar (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This scale is commonly used to assess pain in adults. Using VAS by an observer in order to assess pain in children is commonly used [ 20 , 21 ] yet controversial. Several studies suggest that VAS assessment in children, especially when performed by an observer is an unreliable measure, [ 22 ] and does not correlate with the child's self-reported level of pain.…”
Section: Discussionmentioning
confidence: 99%